Sharia Financial Literacy and Riba-Based Digital Loan Interest: A PLS-SEM Mediation Analysis - Alfa Rohmatin; Sity Komalla (Scimadly Publishing, 2026)
This study empirically analyzes the effect of Islamic financial literacy on university students' interest in using usurious online loans, while examining the mediating role of consumer behavior within this structural framework. This quantitative study used a classroom-based survey design with purposive sampling and involved 180 active Generation Z students at STIT Al-Azami Cianjur. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) in SmartPLS 4. The results reveal that Islamic financial literacy has a direct, positive, and significant effect on both consumer behavior and interest in usurious online loans. Conversely, consumer behavior has no significant effect on interest in usurious online loans and does not serve as a mediating variable, resulting in a no-mediation model. These findings provide novel empirical evidence on the literacy paradox phenomenon, in which mastering Islamic theoretical knowledge at the cognitive level increases students' perceived behavioral control and technical familiarity in navigating digital financing applications. Furthermore, the absence of a mediating role proves that borrowing decisions on non-Islamic platforms are not driven by wasteful habits or hedonistic lifestyles, but are instead triggered by direct cognitive calculations when facing financial fragility and emergency funding needs. The implications of this study call for a reorientation of financial education strategies in higher education, shifting from theoretical knowledge transfer to instilling self-control and building internal Islamic-based financial assistance ecosystems.